2020
DOI: 10.2166/wst.2020.281
|View full text |Cite
|
Sign up to set email alerts
|

Lead-resistant bacteria isolated from oil wastewater sample for bioremediation of lead

Abstract: Anthropogenic activities such as oil exploration have resulted in an environmental concern as they are comprised of residual hydrocarbons and metals. Following the hypothesis that endogenous bacterial communities have enhanced tolerance to heavy metals, we isolated and characterized culturable lead-resistant bacteria from an oil wastewater sample and determined whether they could reduce lead ions from the medium. The wastewater sample containing indigenous bacteria were taken out from a traditional oil field, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…On the other hand, a reduction of 87% in the concentration of Pb was obtained. Visible morphological modifications were also observed in the Pb-treated samples, with the biomass acquiring a brown color, attributed to the biotransformation of Pb 2+ ions through precipitation catalyzed by phosphatase [ 110 , 111 ]. The high tolerance of the bacterial strain to Pb was positively correlated with its bioremediation efficiency, having the highest tolerance index compared to Zn and Cr as well.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, a reduction of 87% in the concentration of Pb was obtained. Visible morphological modifications were also observed in the Pb-treated samples, with the biomass acquiring a brown color, attributed to the biotransformation of Pb 2+ ions through precipitation catalyzed by phosphatase [ 110 , 111 ]. The high tolerance of the bacterial strain to Pb was positively correlated with its bioremediation efficiency, having the highest tolerance index compared to Zn and Cr as well.…”
Section: Resultsmentioning
confidence: 99%
“…(ID3). Utami et al (2020) reported the isolation of B. cereus strains from contaminated soils, which could tolerate up to 10 mM Pb concentration. Compared to other investigations, the current findings are in consistent with earlier reports.…”
Section: Discussionmentioning
confidence: 99%
“…Characterization of IA4, IA21, and IA23 isolate is an important thing to do to know more about these bacteria. Based on the gram of bacteria, gram-positive bacteria are more tolerant to heavy metals pollutants than gram-negative bacteria [23]. This is related to the cell wall of bacteria in which the cell wall of gram-positive bacteria has a higher capacity to absorb heavy metals than gram-negative bacteria.…”
Section: Pb Maximum Tolerance Of Bacteriamentioning
confidence: 99%
“…The colonies of IA4, IA21, and IA23 isolate had been observed as brown colonies. Brown colonies indicate the mechanism of lead resistance of these bacteria is precipitation that is part of the extracellular mechanism to prevent lead movement on bacterial cell walls [23]. However, further study is needed to ensure the definite mechanism involved in lead resistance of IA4, IA21, IA23 isolate due to some lead-resistance mechanism has been suggested.…”
Section: Pb Maximum Tolerance Of Bacteriamentioning
confidence: 99%